A history of God : the 4000-year quest of Judaism, Christianity and Islam - Armstrong, Karen, 1944- (New York : Ballantine Books, 1994)
Explores the ways in which the'idea' and'experience' of God evolved among monotheists--Jews, Christians and Muslims.
Includes bibliographical references : (pages 427-436) and index.
Keywords: God -- Comparative studies; God -- Biblical teaching; God -- History of doctrines; God (Islam) -- History of doctrines; God (Judaism) -- History of doctrines; Judaism -- Doctrines -- History; Islam -- Doctrines -- History